IDENTIFYING PERFORMANCE BOTTLENECKS IN WORK-STEALING COMPUTATIONS. - Tallent, Nathan R.; Mellor-Crummey, John M. (Computer (00189162), 2009)
The article discusses the authors' implementation of performance analysis methods and tools to resolve a work stealing computation's performance obstacles. Their strategy was implemented in HPCToolkit and it addresses the problem of pinpointing scalability bottlenecks and providing user-level insight on their causes. The key properties of a parallel programming language are noted. The strategy also quantifies parallel idleness and overhead and incurs no measurement overhead.